Photostability and long-term preservation of a colloidal semiconductor-based single photon emitter in polymeric photonic structures. Issue 8 (16th July 2019) - Au, Thi Huong; Buil, Stéphanie; Quélin, Xavier; Hermier, Jean-Pierre; Lai, Ngoc Diep
Abstract : By using a protective polymer matrix, the single photon emission of a single quantum dot becomes perfectly stable. This also opens an excellent accessibility to realisation of photonic quantum devices. Abstract : Colloidal semiconductor quantum dots (QDs) are promising candidates for various applications in electronics and quantum optics. However, they are sensitive and vulnerable to the chemical environment due to their highly dynamic surface with a large portion of exposed atoms. Hence, oxidation and detrimental defects on the nanocrystal (NC) interface dramatically deteriorate their optical as well as electrical properties. In this study, a simple strategy is proposed not only to obtain good preservation of colloidal semiconductor QDs by using a protective polymer matrix but also to provide excellent accessibility to micro-fabrication by optical lithography. A high-quality QD–polymer nanocomposite with mono-dispersion of the NCs is synthesized by incorporating the colloidal CdSe/CdS NCs into an SU-8 photoresist. Our approach shows that the oxidation of the core/shell QDs embedded in the SU-8 resist is completely avoidable. The deterministic insertion of multiple QDs or a single QD into photonic structures is demonstrated. Single photon generation is obtained and well-preserved in the nanocomposite and the polymeric structures.